Ganho genético e reação à antracnose em feijoeiro comum (Phaseolus vulgaris L.) - Oliveira, Hudson do Vale de (2011)
This study had the objective to evaluate the agronomic characteristics and reactions to anthracnose from elite lines of "Carioca" common bean grains in Maringá, Paraná. The experiments were conducted during the agricultural years of 2008 and 2010 at experimental area of Irrigation technology Center - CTI. The traits used were composed by 36 elite lines of "Carioca" common bean, designed in lattice 6 x 6, with experimental units formed by two lines of 4.0m of length, spaced with 0.50m. The reaction tests to anthracnose (races 65, 89 and 2047) were carried out under greenhouse conditions and also in a mist chamber for two days at Laboratory Improvement and Bean Research Center of Biotechnology Applied to Agriculture. The following characteristics were evaluated: grain yield (Kg ha-1), number of pods per plant, number of grains per pod and mass of 100 grains. In experiment 1, analysis of variance revealed the presence of significant effect on grain yield (P ≤ 0.01), number of pods per plant (P ≤ 0.01) and the number of grains per pod (P ≤ 0.05), while in experiment 2, all characteristics showed a significant effect (P ≤ 0.01). In the joint analysis, except for the mass of 100 grains, features all the significant effect (P ≤ 0.01). As for reaction to anthracnose, it was found that most strains showed a resistance index of 66.7%. The smaller index of virulence was shown the race 65 (16.7%). Therefore, this study found that the combination of strains MAIV-18.264, MAIV-18.259, RCII-2.21, RCII-6.14, CVIII-3, PF-5.3, and Ouro Negro is indicated for the implementation of a breeding program aimed the increase in grain production and resistance to anthracnose.